Supersoft X-ray phases of recurrent novae as an indicator of their white dwarf masses. (4th August 2020) - Kato, Mariko; Hachisu, Izumi
Abstract: We have examined the optical/X-ray light curves of seven well-observed recurrent novae, V745 Sco, M31N 2008-12a, LMC N 1968, U Sco, RS Oph, LMC N 2009a, T Pyx, and one recurrent nova candidate LMC N 2012a. Six novae out of the eight show a simple relation that the duration of supersoft X-ray source (SSS) phase is 0.70 times the total duration of the outburst (= X-ray turnoff time), i.e., t SSS = 0.70  t off, the total duration of which ranges from 10 to 260 d. These six recurrent novae show a broad rectangular X-ray light curve shape, the first half-period of which is highly variable in the X-ray count rate. The SSS phase also corresponds to an optical plateau phase that indicates a large accretion disk irradiated by a hydrogen-burning white dwarf (WD). The two other recurrent novae, T Pyx and V745 Sco, show a narrow triangular-shaped X-ray light curve without an optical plateau phase. Their relations between t SSS and t off are rather different from the above six recurrent novae. We also present theoretical SSS durations for recurrent novae with various WD masses and stellar metallicities ( Z = 0.004, 0.01, 0.02, and 0.05) and compare them with the observed durations of these recurrent novae. We show that SSS duration is a good indicator of WD mass in recurrent novae with a broad rectangular X-ray light curve shape.